Corporate governance dynamics: How audit committees and board characteristics influence firm value through audit report lag? - Kurnia, Lusi; Saifi, Muhammad; Damayanti, Cacik Rut (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2024)
This study investigates the impact of corporate governance attributes, particularly the board of directors and audit committee, on the firm value of property and real estate companies in Indonesia. Additionally, this study introduces the novel exploration of audit report lag as a mediating factor in the relationship between corporate governance and firm value. Utilizing a quantitative approach, secondary data were extracted from the financial statements of property and real estate companies. The study employed a purposive sampling technique, resulting in a sample of 26 companies listed on the IDX for 2018-2022. In this study, inferential statistical analysis is conducted using the Partial Least Squares (PLS) based Structural Equation Modeling (SEM) technique. The findings reveal that corporate governance attributes, including the board of directors and audit committee, significantly enhance firm value. Furthermore, audit report lag mediates the effect of the audit committee on firm value but does not mediate the effect of the board of directors. This implies that while the audit committee plays a crucial role in reducing audit report lag, thereby enhancing firm value, the board of directors may influence firm value through different mechanisms not captured by audit report lag.